Responsive Interior: Tactics for Adaptation and Resilience - Atmodiwirjo, Paramita; Yatmo, Yandi Andri (Interiority, 2022)
Design disciplines continuously face challenges to demonstrate resilience in responding to rapid changes and complex issues in our contemporary world. The idea of responsive interior highlights the ability to respond appropriately to a particular context through various tactics to ensure its relevance and resilience for the present and future. Interior practices deal with intervention, adaptation, and alteration of existing conditions, as well as finding new uses and programmes that can be added to existing spaces. Behind such attempts, a series of responsive tactics has become necessary to gather knowledge and understanding of the existing qualities, which should be an important basis for appropriate interior programming as a tactical response. This issue of Interiority presents a collection of ideas and explorations that demonstrate various acts of adaptation performed in different interior contexts, as well as various tactical interior approaches to reuse and repurpose the existing. While the world is changing quickly, the interior design discipline must strengthen its capability to respond and adapt. Finding more tactics for new interior programming, reading thoroughly into the existing, exploring various forms of adaptability, and establishing more creative design thinking become crucial steps towards interior resilience in a constantly changing world.